Implementation of the pancasila student profile strengthening project on sustainable lifestyle themes - Tiyani, Tri Agus; Ramadan, Zaka Hadikusuma (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2024)
This research aims to analyze the implementation of the project to strengthen the profile of Pancasila students with the theme of a sustainable lifestyle in the independent curriculum in class V of SD Negeri 04 Bungaraya. The research method used is qualitative with a phenomenological approach. Qualitative research is carried out by utilizing various methodologies currently available in nature with the aim of interpreting the phenomena seen. Qualitative research is research that uses the natural environment with the aim of interpreting phenomena that occur, and is carried out using various existing methods. Participants included 2 class V homeroom teachers, 4 class V students, and the principal of SDN 04 Bungaraya. Data were collected through observation, interviews, and documentation in May 2024. Data analysis was carried out by Miles and Huberman using a data reduction process, presenting important data, and drawing conclusions. The research results show that the implementation of the P5 sustainable lifestyle theme at SDN 04 Bungaraya was carried out in 3 stages: planning stage, implementation stage and evaluation stage. 1) The planning stage includes several activities, namely preparing the learning ecosystem, designing P5, designing modules, and preparing facilities and infrastructure; 2) The implementation stage includes project introduction, conceptual, contextual and project action; 3) The evaluation stage includes diagnostic assessment, formal assessment, summative assessment, and follow-up. The implementation of the P5 sustainable lifestyle theme has a positive impact on preparing students to face future challenges and have sustainable behavior towards the environment.